An updated map of infauna associations for the southeastern North Sea with high spatial resolution inside Marine Protected Areas - Lars Gutow; Marko Rothe; Valentin Sauerbier; Tim Bildstein; Lasse Sander; Javier Lenzi; Chueh-Chen Tung; Jan Beermann; Kathrin Heinicke; Roland Pesch (Regional Studies in Marine Science, 2026)

Characterization and differentiation of sublittoral sandbanks in the southeastern North Sea - Jan Beermann; Lars Gutow; Steffen Wührdemann; Rebecca Konijnenberg; Kathrin Heinicke; Tim Bildstein; Sandra Jaklin; Manuela Gusky; Michael L. Zettler; Jennifer Dannheim; Roland Pesch (Biodiversity and Conservation, 2023)
Marine sublittoral sandbanks are essential offshore feeding grounds for larger crustaceans, fish and seabirds. In the southern North Sea, sandbanks are characterized by considerable natural sediment dynamics and are subject to chronic bottom trawling. However, except for the Dogger Bank, sandbanks in the southeastern North Sea have been only poorly investigated until now. We used an extensive, multi-annual dataset covering ongoing national monitoring programmes, environmental impact assessments, and basic research studies to analyse benthic communities on sublittoral sandbanks, evaluating their ecological value against the backdrop of similar seafloor habitats in this region. The analysis revealed complex spatial structuring of sandy seafloor habitats of the southeastern North Sea. Different infauna clusters were identified and could be specified by their composition of characteristic species. The sandbanks shared common structural features in their infauna community composition although they were not necessarily characterized by particularly high biodiversity compared to other sandy habitats. A close association of one of the main bioturbators in the southern North Sea, the sea urchin Echinocardium cordatum , with sandbanks was detected, which may promote the sediment-bound biogeochemical activity in this particular seafloor habitat. This would corroborate the status of sandbanks as sites of high ecological value calling for consideration in marine conservation.